Rechtstaat dan Konstitusionalisme dalam Pemikiran Abdurrahman Wahid (1940-2009) dan Hasyim Muzadi (1944-2017) - Mustofa, Mustofa (Madania: Jurnal Kajian Keislaman, 2018)
Abstract: Rechtstaat and Constitutionalism in the Thought of Abdurrahman Wahid (1940-2009) and Hasyim Muzadi (1944-2017). This study aims to explore the thoughts of Abdurrahman Wahid and Hasyim Muzadi about rechtstaat and constitutionalism. This study uses the juridical-normative method with the historical-normative approach and the type of qualitative data. The data sources consist of primary, secondary, and tertiary data obtained from the number of literature and documentation. While the data collection techniques are obtained from book reviews and documentation. Data analysis method is conducted deductively and inductively. The result of this study reveals that the state law and the constitutionalism in the thoughts of Abdurrahman Wahid and Hasyim Muzadi refer to the constitution of Madinah and civil society in relation to religion and state. Abdurrahman Wahid and Hasyim Muzadi can be positioned as substantial, pluralist, nationalist, and humanist religious thinkers. Abdurrahman Wahid and Hasyim Muzadi’s contribution has proved to give improvements in strengthening the relationship between religion and state in Indonesia and has implications for rechtstaat’s future and constitutionalism in the Islamic legal system in Indonesia. The critical findings of this research are the thoughts of Abdurrahman Wahid, and Hasyim Muzadi provides enlightenment of idea and solution to the problematic rechtstaat with a cultural-religious approach.